Anastomotic Strictures after Esophageal Atresia Repair: Timing of Dilatation during the First Two Postoperative Years - Salö, Martin; Stenström, Pernilla; Anderberg, Magnus; Arnbjörnsson, Einar (The Surgery Journal, 2018)
Background We determined time frames for dilatation of anastomotic strictures (ASs) occurring during the first 2 years after esophageal atresia (EA) repair.Methods A retrospective study was conducted on children with EA (Gross type C) who underwent direct repair between January 2008 and March 2015 at a single tertiary center of pediatric surgery. Endoscopic signs of stricture were indications for dilatation because the endoscopy provides more reliable information than X-ray imagining methods.Results Among our cohort of 49 children with EA, 19 (39%) required at least one esophageal dilatation. All children required initial dilatation within the first year of life and none was older than 1 year during initial dilatation (p < 0.01). A median of three dilatations (range: 1–13) took place per patient, with 87% performed during the first postoperative year. The timing of initial dilatation in the first year (< 6 months, 14/19 [74%] vs. 6–12 months, 5/19 [26%]) was predictive of the need for dilatation beyond the first year (9/14 [64%] vs. 0/5 [0%]; p = 0.03) but not of more numerous dilatations (median, 3 vs. 1; p = 0.07).Conclusion The need for dilatation within 6 months postoperatively predicts the need for dilatation after 1 year, but it does not indicate the number of dilatations that will be needed.
Keywords: esophageal atresia; anastomotic stricture; balloon dilatation timing; infants